Evaluation of Ebselen-azadioxatriangulenium as redox-sensitive fluorescent intracellular probe and as indicator within a planar redox optode. (February 2020) - Koren, Klaus; Gravesen Salinas, Nina Katharina; Santella, Marco; Moßhammer, Maria; Müller, Marie-Caroline; Dmitriev, Ruslan I.; Borisov, Sergey M.; Kühl, Michael; Laursen, Bo W.
Abstract: Redox homeostasis is essential for cellular survival and is therefore tightly regulated. Visualizing changes in the local redox state is essential for detecting oxidative stress, especially with the help of red, long emission lifetime probes. We synthesized a new reversible, redox-sensitive fluorescent probe, ebselen-azadioxatriangulenium (Ebselen-ADOTA), and characterized its potential use for intra- and extracellular redox sensing. The probe consists of a photostable triangulenium-based fluorophore (emission maximum at 564 nm) modulated by a redox-active ebselen motif. The reduced form only shows around 1/10 of the emission intensity of the oxidized form. The Ebselen-ADOTA probe exhibited reversible oxidation and reduction in solution under extracellular conditions. In addition, Ebselen-ADOTA can visualize an increase in oxidative stress within anaerobic bacteria when exposing them to air, the probe did not readily respond to changes in the redox environment inside mammalian cells, probably due to unfavorable localization, aggregation or binding to cysteine containing proteins. When incorporated inside a polymer matrix (hydrogel D4 mixed with poly(acrylic acid)), the probe showed a rapid and fully reversible response to redox changes, thus enabling the preparation of a redox-sensitive optode. Highlights: Synthesis and photophysical characterization of the redox probe Ebselen-ADOTA. Detailed characterization of the reaction kinetics and products. Intracellular redox sensing within bacterial and mammalian cells. Preparation of the first redox optode.